Antimicrobial resistance profile of Staphylococcus aureus isolates obtained from skin and soft tissue infections of outpatients from a university hospital in Recife -PE, Brazil Perfil de resistência antimicrobiana de isolados de Staphylococcus aureus provenientes de infecções de pele e tecidos moles de pacientes ambulatoriais de um hospital universitário em Recife - PE, Brasil - Fabiana Beserra Caraciolo; Maria Amélia Vieira Maciel; Josemir Belo dos Santos; Marcelle Aquino Rabelo; Vera Magalhães (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Staphylococcus aureus has a notable ability to acquire resistance to antibiotics, and methicillin resistance represents a growing public health problem. Methicillin-resistant S. aureus (MRSA) has also become important outside the hospital environment, particularly in the United States. In Brazil, since 2005, cases of community skin infections caused by MRSA have been reported, but resistance studies involving outpatients are scarce. OBJECTIVE: To know the resistance profile of S. aureus involved in skin and soft tissue infections of patients seen at the Dermatology outpatient clinic of a university hospital in Recife, Pernambuco State, northeastern Brazil. METHODS: Prospective study involving 30 patients with skin and soft tissue infections, seen at the Dermatology outpatient clinic from May until November 2011. To evaluate the susceptibility of S. aureus to antibiotics, the disk diffusion method and oxacillin screening agar were used. RESULTS: From a total of 30 samples of skin lesions, 19 (63%) had positive culture for S. aureus. The following resistance patterns of S. aureus were observed: penicillin, 95%; tetracycline, 32%; erythromycin, 21%; gentamicin, 16%; cefoxitin, 11%; oxacillin, 11%; trimethoprim-sulfamethoxazole, 11%; chloramphenicol, 11%; clindamycin, 5% ; and ciprofloxacin, 0%. One of the identified MRSA was obtained from a patient without risk factors for its acquisition, and was resistant, beyond to the beta-lactams, only to tetracycline. CONCLUSIONS: With regard to the resistance patterns of S. aureus, resistances to tetracycline, erythromycin and gentamicin were the highest. It was documented, for the first time in Pernambuco, a case of skin infection caused by community-associated MRSA. FUNDAMENTOS: O Staphylococcus aureus possui uma notável habilidade de adquirir resistência antimicrobiana, sendo a resistência à meticilina um problema de saúde pública crescente. O S. aureus resistente à meticilina (MRSA) vem se tornando importante também fora do ambiente hospitalar, particularmente nos Estados Unidos. No Brasil, desde 2005, têm sido relatados casos de infecções cutâneas comunitárias causadas por MRSA, porém estudos de resistência envolvendo pacientes ambulatoriais são escassos. OBJETIVO: Conhecer o perfil de resistência de S. aureus envolvidos em infecções de pele e partes moles de pacientes atendidos no ambulatório de Dermatologia de um hospital universitário de Recife, Pernambuco. MÉTODO: Estudo prospectivo envolvendo 30 pacientes com infecções de pele e tecidos moles atendidos no ambulatório de Dermatologia de maio a novembro de 2011. Para avaliação da suscetibilidade dos S. aureus aos antibióticos foram utilizados teste de disco-difusão e placa de screening de oxacilina. RESULTADOS: Das 30 amostras analisadas, 19 (63%) tiveram cultura positiva para S. aureus. Os seguintes padrões de resistência dos S. aureus foram observados: penicilina, 95%; tetraciclina, 32%; eritromicina, 21%; gentamicina, 16%; cefoxitina, 11%; oxacilina, 11%; sulfametoxazol-trimetoprima, 11%; clorafenicol, 11%; clindamicina, 5%; e ciprofloxacina, 0%. Um dos MRSA identificados foi obtido de paciente sem fatores de risco para sua aquisição, e além de aos betalactâmicos, mostrou-se resistente apenas à tetraciclina. CONCLUSÕES: Em relação aos padrões de resistência dos S. aureus, destacaram-se as resistências à tetraciclina, eritromicina e gentamicina. Documentou-se, pela primeira vez em Pernambuco, um caso de infecção cutânea causada por MRSA associado à comunidade.